Express Assessment of Apatite Content in Apatite–Nepheline Ores of Ultrabasic Alkaline Complexes Based on Its Luminescent Properties (The First Study Stage) - Darya N. Shibaeva; Alena A. Kompanchenko; Victor V. Bulatov; Danil A. Asanovich (Minerals, 2022)
The article presents the results of the first study stage aimed at analyzing the luminescent properties of the main and minor minerals composing the apatite–nepheline ores and host rocks in the deposits of the Khibiny rock massif (Kola Peninsula, Russia). The main purpose of the work was a search of a stable identification feature providing fast and safe determination of fluorapatite in the mineral mixture of apatite–nepheline ores and solving technological tasks, namely sampling the borehole walls in open pits. The first stage includes studies carried out on pure mono-fractions of four minerals occurring in fluorapatite deposits and possessing obvious luminescent properties: fluorapatite, nepheline, calcite, and sodalite. The authors have revealed luminescence spectra of these minerals and established correlation of their spectral characteristics with the literature data and their consistency. However, the high intensity of sodalite luminescence in a wide band can complicate identification of fluorapatite by the luminescence spectrum in many cases. Therefore, it is reasonable to use the color and intensity of luminescence rather than spectral characteristics.